Pengarih Pendapatan Asli Daerah, Dana Alokasi Umum Dan Dana Alokasi Khusus Terhadap Belanja Modal Pada Provinsi Sumatera Barat Tahun 2018-2022 - Eko Rinando; Muhammad Rivandi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to examine the influence of Regional Original Income, General Allocation Funds and Special Allocation Funds on Capital Expenditures in West Sumatra Province in 2018-2022. The research population is 12 districts and 7 cities in West Sumatra, with sampling using the census method where the entire population will be used as a sample. The regression method uses Panel Regression. Based on the research results, it shows that Regional Original Income has no effect on Capital Expenditures, General Allocation Funds have a positive effect on Capital Expenditures and Special Allocation Funds have no effect on Capital Expenditures.